PENGARUH KOMUNIKASI DAN MOTIVASI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA SMP SATU ATAP NEGERI 4 PANGURURAN - Risma Hartati (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
The purpose of this study was to determine the influence of communication and parental motivation on the learning achievement of the eight grade SMP Satu Atap Negeri 4 Pangururan 2018/2019 academic year. This type of research is ex-post facto research. The sample used was 39 students, while the taking technique used the total sampling method. The data usage technique used is by observation, questionnaire and documentation. Validation test for questionnaire analysis using product moment correlation formula, reliability is calculated using the Cronbach alpha formula. The analysis technique used is the t test and the F test. Based on the results of data analysis using the SPSS 20 program obtained with multiple linear regression Y = 36.253 + 0.693 X1 + 0.356 X2 then the parent communication variable (X1) has a significant positive fan influence on the learning achievement (Y) with tcount> t table (3.789> 0.682) and sig <0.05 (0.001 <0.05), while parental motivation (X2) also has a positive and significant effect on the achievement index with tcount> t table (2,164> 0,681) and sig <0,05 (0,037 <0,05) together communication and parental motivation have a positive and significant effect on the achievement index with the values of Fcount> Ftable (139,294> 4,11) and sig < 0.05 (0,000 <0,05). The percentage contribution to the influence of communication and parental motivation on student learning achievement is 89%.